2013
DOI: 10.1128/aac.00283-13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Combinations of 4′-Ethynyl-2-Fluoro-2′-Deoxyadenosine with Clinically Used Antiretroviral Drugs

Abstract: i Drug combination studies of 4=-ethynyl-2-fluoro-2=-deoxyadenosine (EFdA) with FDA-approved drugs were evaluated by two different methods, MacSynergy II and CalcuSyn. Most of the combinations, including the combination of the two adenosine analogs EFdA and tenofovir, were essentially additive, without substantial antagonism or synergism. The combination of EFdA and rilpivirine showed apparent synergism. These studies provide information that may be useful for the design of EFdA combination regimens for initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Previously, we have shown that a series of 4Ј-substituted analogs with a 3Ј-OH possess anti-HIV activity (9 -11). EFdA is the most potent of this series and, to our knowledge, the most potent NRTI with subnanomolar EC 50 both in T-cells and peripheral blood mononuclear cells (10,11,16). The strong potency of EFdA is the result of its unique mechanism of action as well as its resistance to degradation by adenosine deaminase (15).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previously, we have shown that a series of 4Ј-substituted analogs with a 3Ј-OH possess anti-HIV activity (9 -11). EFdA is the most potent of this series and, to our knowledge, the most potent NRTI with subnanomolar EC 50 both in T-cells and peripheral blood mononuclear cells (10,11,16). The strong potency of EFdA is the result of its unique mechanism of action as well as its resistance to degradation by adenosine deaminase (15).…”
Section: Discussionmentioning
confidence: 96%
“…We have shown that EFdA is resistant to degradation by adenosine deaminase, providing an enhanced half-life to the compound compared with other NRTIs (11,15). EFdA is very effective not only against wild-type HIV but also against drug-resistant strains and has displayed synergistic antiviral effects when combined with other inhibitors such as the recently approved second generation non-NRTI rilpivirine (16). We have also shown that EFdA is significantly better than tenofovir (TFV), zidovudine, and emtricitabine in blocking simian immunodeficiency virus replication in monkey peripheral blood mononuclear cells and that it was highly effective at treating simian immunodeficiency virus infection and AIDS symptoms in simian immunodeficiency virus-infected macaques with advanced AIDS with no apparent signs of toxicity (17).…”
mentioning
confidence: 99%
“…They generally lack a 3=-OH group and thus act as chain terminators upon incorporation into viral DNA by reverse transcriptase (RT) (26)(27)(28)(29). However, 4=-ethynyl-2-fluoro-2=-deoxyadenosine (EFdA) retains a 3=-OH group, acts primarily by blocking RT translocation following incorporation of EFdA monophosphate (MP) into the template-primer, and has picomolar antiviral potency (30)(31)(32)(33)(34)(35)(36)(37). NRTIs are administered as nucleosides and are phosphorylated to their active forms by cellular kinases (38).…”
Section: H Uman Immunodeficiency Virus Type 1 (Hiv-1) Replicates Primmentioning
confidence: 99%
“…EFdA is effective against wild-type and clinical drug-resistant HIV strains (6), and acts synergistically with the second-generation nonnucleoside RT inhibitor rilpivirine (13). EFdA blocks simian immunodeficiency virus replication in vitro in macaque PBMCs better than tenofovir (TFV), zidovudine (AZT), and emtricitabine (FTC) (14).…”
mentioning
confidence: 99%